2017
DOI: 10.1139/cjfas-2016-0396
|View full text |Cite
|
Sign up to set email alerts
|

Mercury bioaccumulation increases with latitude in a coastal marine fish (Atlantic silverside,Menidia menidia)

Abstract: Human exposure to the neurotoxic methylmercury (MeHg) occurs primarily via the consumption of marine fish, but the processes underlying large-scale spatial variations in fish MeHg concentrations [MeHg], which influence human exposure, are not sufficiently understood. We used the Atlantic silverside (Menidia menidia), an extensively studied model species and important forage fish, to examine latitudinal patterns in total Hg [Hg] and [MeHg]. Both [Hg] and [MeHg] significantly increased with latitude (0.014 and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
3
17
0
Order By: Relevance
“…The link between MeHg bioaccumulation and bioenergetics is most commonly exhibited through growth dilution, whereby Hg concentrations are lower in faster growing individuals with higher growth efficiency than those that grow more slowly and have lower growth efficiency. This process has been demonstrated in both fish (Ward et al 2010 ) and birds (Ackerman et al 2011 ), and is commonly visible in the negative relationship between Hg concentrations and body condition (Eagles-Smith et al 2016b ; Baumann et al 2017 ). Growth efficiency and associated bioenergetics can be influenced by either changes in basal metabolic rate (Dijkstra et al 2013 ), activity costs, or food quality (Lepak et al 2012 ; Johnson et al 2015 ; Karimi et al 2016a ).…”
Section: Domain 1: Extrinsic Global Change Drivers That Influence Metmentioning
confidence: 93%
“…The link between MeHg bioaccumulation and bioenergetics is most commonly exhibited through growth dilution, whereby Hg concentrations are lower in faster growing individuals with higher growth efficiency than those that grow more slowly and have lower growth efficiency. This process has been demonstrated in both fish (Ward et al 2010 ) and birds (Ackerman et al 2011 ), and is commonly visible in the negative relationship between Hg concentrations and body condition (Eagles-Smith et al 2016b ; Baumann et al 2017 ). Growth efficiency and associated bioenergetics can be influenced by either changes in basal metabolic rate (Dijkstra et al 2013 ), activity costs, or food quality (Lepak et al 2012 ; Johnson et al 2015 ; Karimi et al 2016a ).…”
Section: Domain 1: Extrinsic Global Change Drivers That Influence Metmentioning
confidence: 93%
“…Pathways of methylmercury (MeHg) bioaccumulation in fish and the environmental factors that control them are not sufficiently understood in estuarine and coastal ecosystems (Baumann et al, 2017;Eagles-Smith et al, 2018;Schartup et al, 2018) where much of the seafood consumed by humans is harvested (Sheehan et al, 2014;Sunderland, 2007). Estuaries are critical habitats supporting a multitude of benthic and pelagic species, including both resident and transient fish (Deegan et al, 2000;Kneib, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Productivity in estuaries may therefore decrease bioaccumulation due to bloom dilution (Driscoll et al, 2012 ;Luengen and Flegal, 2009) or increase MeHg in the biota due to higher MeHg production (Soerensen et al, 2016;Stoichev et al, 2016). Past studies have shown that latitudinal or temperature differences influence MeHg bioaccumulation: higher MeHg concentrations in estuarine fish have been linked with more northern latitudes (Baumann et al, 2017), where Hg biomagnification is highest (Lavoie et al, 2013). Under controlled conditions, increased temperature has been found to increase MeHg bioaccumulation in estuarine fish (Dijkstra et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This particular species can be thought of as an example, given that it is a very important fish species within seagrass meadows in Sweden, and therefore declines in cod numbers have the potential to threaten other shallow-water coastal habitats. Due to its high mobility and use of large areas, the species connects many habitats throughout its lifetime, both within the shallow-water coastal areas and across nearshore-offshore seascapes [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%